2023
DOI: 10.1096/fj.202300223r
|View full text |Cite
|
Sign up to set email alerts
|

A LGR5 reporter pig model closely resembles human intestine for improved study of stem cells in disease

Abstract: Intestinal epithelial stem cells (ISCs) are responsible for intestinal epithelial barrier renewal; thereby, ISCs play a critical role in intestinal pathophysiology research. While transgenic ISC reporter mice are available, advanced translational studies lack a large animal model. This study validates ISC isolation in a new porcine Leucine Rich Repeat Containing G Protein-Coupled Receptor 5 (LGR5) reporter line and demonstrates the use of these pigs as a novel colorectal cancer (CRC) model. We applied histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 87 publications
(269 reference statements)
0
15
0
Order By: Relevance
“…In fact, the pig APC 1311 model has been used in the development of cathepsin protease-activatable probe for fluorescence-guided endoscopy [ 79 ], fluorescent silica nanoparticles-guided detection of colorectal adenomas using video-rate fluorescence-assisted white-light endoscopy [ 80 ], and to train artificial intelligence to detect more adenomas [ 81 ]. Colonoscopies are imperative in the early detection of colonic dysplasia [ 30 , 75 ]. Furthermore, a recent study has indicated the utility of pig as a translational intestinal epithelial stem cell (ISC) research model.…”
Section: Porcine Models Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the pig APC 1311 model has been used in the development of cathepsin protease-activatable probe for fluorescence-guided endoscopy [ 79 ], fluorescent silica nanoparticles-guided detection of colorectal adenomas using video-rate fluorescence-assisted white-light endoscopy [ 80 ], and to train artificial intelligence to detect more adenomas [ 81 ]. Colonoscopies are imperative in the early detection of colonic dysplasia [ 30 , 75 ]. Furthermore, a recent study has indicated the utility of pig as a translational intestinal epithelial stem cell (ISC) research model.…”
Section: Porcine Models Of Cancermentioning
confidence: 99%
“…In contrast, in mouse Olfm4 expression is restricted only to the small intestinal ISCs. Therefore, an OLFM4 producing porcine model could provide important data for modeling CRC where OLFM4 is a known marker for cancer cells and potential metastasis [ 30 ]. Schaaf et al (2022) extensively reviewed available models of CRC such as TP53 R167H and KRAS G12D [ 75 ].…”
Section: Porcine Models Of Cancermentioning
confidence: 99%
“…This perpetual movement of intestinal epithelial cells (IEC) is driven by the continuous asymmetric division of intestinal stem cells (ISC) nested at the bottom of intestinal crypts. These LGR5+ cells generate progenitor cells, characterized by the presence of Sox9 [6]. These cells then differentiate into different cell lineages as they migrate up the crypt-villus axis in the small intestine and up the crypt in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, using gene edited, Lgr5 + cells have been identified in various tissues, including the intestinal epithelium, pancreatic ductal cells, lungs, prostate gland, hair follicles, eyes, cochlea, tongue, and others ( Leung et al, 2018 ). It has been shown in multiple tissues including gastrointestinal, lung, cochlea, and skin that LGR5 + cells have the ability to generate organoids with multiple cell types ( Sato et al, 2011 ; Koo and Clevers, 2014 ; Mclean et al, 2017 ; Polkoff et al, 2022a ; Schaaf, et al, 2023 ). Additionally, as will be described below in more detail, others have shown that LGR5 cells have regenerative capacity on a wide range of tissue and can participate in tissue repair after injury and during homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…This unique stem cell niche is maintained primarily through Wnt secretion, with Paneth cells and myofibroblasts playing a key role in this process ( Sato et al, 2011 ; Kabiri et al, 2014 ). In mouse intestines, as in humans and pigs, Lgr5 is present at the crypt base, where it can generate all cell types found on the villus ( Sato et al, 2011 ; Schaaf, et al, 2023 ). Though Lgr5 does not appear crucial for the maintenance of healthy mouse intestinal epithelium, it is essential in tissue recovery post-injury.…”
Section: Introductionmentioning
confidence: 99%